Fetal Cytokine Balance, Erythropoietin and Thalassemia but Not Placental Malaria Contribute to Fetal Anemia Risk in Tanzania - Kabyemela, Edward R.; Fried, Michal; Kurtis, Jonathan D.; Moses, Gwamaka; Gorres, J. Patrick; Muehlenbachs, Atis; Duffy, Patrick E. (Frontiers in Immunology, 2021)
Fetal anemia is common in malarious areas and a risk factor for anemia as well as mortality during infancy. Placental malaria (PM) and red cell abnormalities have been proposed as possible etiologies, but the relationship between PM and fetal anemia has varied in earlier studies, and the role of red cell abnormalities has not been studied in malarious areas. In a Tanzanian birth cohort, we determined PM status, newborn red cell abnormalities, and maternal and cord blood levels of iron regulatory proteins, erythropoietin (EPO), cytokines and cytokine receptors. We examined the relationship between these factors and fetal anemia. Fetal anemia was present in 46.2% of the neonates but was not related to PM. Maternal iron deficiency was common (81.6%), was most frequent in multigravidae, and interacted with gravidity to modify risk of fetal anemia but was not directly related to risk. Among offspring of iron-deficient women, the odds of fetal anemia increased with fetal a-thalassemia, increasing cord IL-6 and decreasing cord TNF-RI levels, but these effects varied with gravidity. The EPO response to fetal anemia was low or absent and EPO levels were significantly decreased in newborns with the most severe anemia. This study from an area of high malaria transmission provides evidence that 1) fetal a-thalassemia and cytokine balance but not PM at delivery are related to fetal anemia; 2) maternal iron deficiency increases the risk that other factors may cause fetal anemia; and 3) fetal anemia prevalence and associated risk factors vary by maternal gravidity, suggesting a multifactorial etiology that may require a variety of interventions tailored to different groups.